Quba Curriculum: Modernizing Education through Transformative Leadership at Diniyyah Puteri Islamic Boarding School - Rini Wisda; Rimin Rimin; Yelni Erniyati (Ta'dib, 2026)
This study examines how the modernization of Islamic education emerged through transformative leadership at Diniyyah Puteri Islamic Boarding School. Using a descriptive qualitative case study design, the research emphasizes a comprehensive understanding of the characteristics, conditions, and phenomena related to educational transformation. Data were collected through in-depth interviews, participatory observation, and documentation. The findings reveal that the modernization process of Islamic education at Diniyyah Puteri is reflected in the development and implementation of an adaptive curriculum, namely the Quba curriculum. This curriculum represents the integration of transformative leadership through key leadership dimensions: influence, inspiration, intellectual stimulation, and visionary thinking. These dimensions are manifested in a clear vision and mission that guide all elements of the educational institution. The Quba curriculum is grounded in the Qur’an and Hadith, aiming to shape students’ cognitive, emotional, and spiritual capacities. Its impact can be observed in students’ attitudes, character formation, and knowledge development. The curriculum is implemented through integrated learning activities both in classrooms and dormitory life, creating a holistic educational environment. This modernization reflects an adaptive effort within the Islamic education system to balance intellectual and emotional-spiritual intelligence in response to globalization. The study recommends broader collaboration with public schools and external institutions to foster innovative and adaptive curriculum development. This research contributes to the renewal of Islamic education systems by integrating scientific and technological advancements to prepare adaptive and competitive graduates.